Leptin Gene Protects Against Cold Stress in Antarctic Toothfish - Wang, Ying; Wang, Huamin; Hu, Linghong; Chen, Liangbiao (Frontiers in Physiology, 2021)
Leptin is a cytokine-like peptide, predominantly biosynthesized in adipose tissue, which plays an important role in regulating food intake, energy balance and reproduction in mammals. However, its function is unclear in polar fish. Here, we identified a leptin-a gene (lepa) in the cold-adapted and neutrally buoyant Antarctic toothfish Dissostichus mawsoni that encodes a polypeptide carrying four α-helices and two cysteine residues forming in-chain disulphide bonds, structures shared by most vertebrate leptins. Quantitative RT-PCR confirmed that mRNA levels of the leptin-a gene of D. mawsoni (DM-lepa) were highest in muscle, followed by kidney and liver; detection levels were low in the gill, brain, intestine, and ovary tissues. Compared with leptin-a genes of fishes living in warmer waters, DM-lepa underwent rapid evolution and was subjected to positive selection. Over-expression of DM-lepa in the zebrafish cell line ZFL resulted in signal accumulation in the cytoplasm and significantly increased cell proliferation both at the normal culture temperature and under cold treatment. DM-lepa over-expression also reduced apoptosis under low-temperature stress and activated the STAT3 signalling pathway, in turn upregulating the anti-apoptotic proteins bcl2l1, bcl2a, myca and mdm2 while downregulating the pro-apoptotic baxa, p53 and caspase-3. These results demonstrate that DM-lepa, through STAT3 signalling, plays a protective role in cold stress by preventing apoptotic damage. Our study reveals a new role of lepa in polar fish.